2012
DOI: 10.1108/09654281211253443
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of school health promotion: consequences for professional assistance

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Most often, however, reasons for non-participation mentioned were lack of time and lack of interest, which is often the case in many schools in the Netherlands, since health promotion is not integrated into the Dutch school curriculum [10,58,59]. This clearly implies a need for health promoting policies to outline the need for adoption of evidence-based smoking prevention programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most often, however, reasons for non-participation mentioned were lack of time and lack of interest, which is often the case in many schools in the Netherlands, since health promotion is not integrated into the Dutch school curriculum [10,58,59]. This clearly implies a need for health promoting policies to outline the need for adoption of evidence-based smoking prevention programs.…”
Section: Discussionmentioning
confidence: 99%
“…Second, of the 1380 schools approached, only 89 agreed to participate, which may reveal an overall negative climate toward smoking prevention in the Netherlands and/or to participating in experimental studies. Most often, however, reasons for non-participation mentioned were lack of time and lack of interest, which is often the case in many schools in the Netherlands, since health promotion is not integrated into the Dutch school curriculum [ 10 , 58 , 59 ]. This clearly implies a need for health promoting policies to outline the need for adoption of evidence-based smoking prevention programs.…”
Section: Discussionmentioning
confidence: 99%
“…However, this mediation has not yet been quantitatively assessed. In addition, previous studies provide some indications for a direct impact of the DISC factors on the implementation of the HSA in schools (Boot et al, 2010;Boot and De Vries, 2012).…”
Section: Comprehensive School Health Promotionmentioning
confidence: 99%
“…However, this mediation has not yet been quantitatively assessed. In addition, previous studies provide some indications for a direct impact of the DISC factors on the implementation of the HSA in schools (Boot et al, 2010;Boot and De Vries, 2012 two-year trajectory. The five HSA collaborations were diagnosed by means of a survey among the relevant stakeholders from health services, PHSs and municipal authorities (Pucher et al, 2015b).…”
Section: Comprehensive School Health Promotionmentioning
confidence: 99%
“…Hence, health-promotion research to some extent identifies the same kind of success factors identified by leadership research (the importance of teachers' work) but overlooks the importance of leadership practices and multiprofessional coordination. No single profession can carry the change, so it is not enough just to point to the importance of management and the ability to handle complex organisational challenges (Boot and de Vries, 2010); there needs to be research on what works and why.…”
Section: The Holistic Health Approachmentioning
confidence: 99%